Development of novel SSR molecular markers using a Next-Generation Sequencing approach (ddRADseq) in Stetsonia coryne (Cactaceae) - GUTIÉRREZ,ANGELA VERÓNICA (2021)
Abstract The Cactaceae family is native to the American continent with several centers of diversity. In South America, one of these centers is the Central Andes and many species are considered to be threatened or vulnerable according to the International Union for Conservation of Nature (IUCN). Stetsonia coryne is an emblematic giant columnar cacti of the Chaco phytogeographic province. It has an extensive geographical distribution in many countries of the continent. However, to date there are no specific molecular markers for this species, neither reports of population genetic variability studies, such as for many cactus species. The lack of information is fundamentally due to the lack of molecular markers that allow these studies. In this work, by applying a Genotyping by Sequencing (GBS) technique, we developed polymorphic SSR markers for the Stetsonia coryne and evaluated their transferability to phylogenetically close species, in order to account for a robust panel of molecular markers for multispecies-studies within Cactaceae.